2015
DOI: 10.1002/jor.22776
|View full text |Cite
|
Sign up to set email alerts
|

Effects of steroids on thrombogenic markers in patients undergoing unilateral total knee arthroplasty: A prospective, double‐blind, randomized controlled trial

Abstract: Venous thromboembolism (VTE) remains an important complication after total knee arthroplasty (TKA). Systemic thrombin generation starts perioperatively. Inflammation, characterized by a rise in interleukin-6 (IL6), initiates the coagulation cascade, but low-dose steroids can reduce post-TKA IL6 levels. This double-blinded, randomized, placebo-controlled study enrolled 30 patients undergoing unilateral TKA to assess the effect of perioperative steroids on serum prothrombin fragment (PF1.2), a marker of thrombin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 29 publications
0
28
0
Order By: Relevance
“…Six studies analyzed the levels of inflammatory factors of CRP or IL-6 [14, 16, 20, 2224]. One study each assessed the levels of thrombogenic markers in TKA [15] or THA [22]. Tables 1 and 2 show the detailed descriptions, and Table 3 shows the risks of bias assessment of included studies.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Six studies analyzed the levels of inflammatory factors of CRP or IL-6 [14, 16, 20, 2224]. One study each assessed the levels of thrombogenic markers in TKA [15] or THA [22]. Tables 1 and 2 show the detailed descriptions, and Table 3 shows the risks of bias assessment of included studies.…”
Section: Resultsmentioning
confidence: 99%
“…All studies assessed delayed wound healing: Koh et al reported two cases of delayed wound healing in steroid group and three cases in control group in TKA [12], and this complication was not founded in any other studies. Two studies and five studies, respectively, provided data on the potential complication of osteonecrosis of femoral head (ONFH) [17, 21] and venous thromboembolic events (VTE) [15, 2023]: except two DVTs (one in control group and one in steroid group) reported by Backes and colleagues [21], the related studies didn’t find any ONFH or VTE cases within follow-up. In addition, five studies each assessed the adverse event of pruritus [14, 16, 20, 22, 24] and the levels of serum glucose on the operation day [14, 16, 2022].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations